Characterization in vitro potency of biological active fractions of seeds, skins and flesh from selected Vitis vinifera L. cultivars and interspecific hybrids. (May 2019) - Tkacz, Karolina; Wojdyło, Aneta; Nowicka, Paulina; Turkiewicz, Igor; Golis, Tomasz
Graphical abstract: Highlights: Phenolic and in vitro biological activity of seeds, skins and flesh of V. vinifera was characterized. Phenolic profile was analyzed using by LC-PDA-MS and UPLC-PDA-FL and 48 compounds were identified. Seeds and red skin samples showed the highest antioxidant activity. Seeds and most skin samples were effective inhibitory activity against α-glucosidase and AChE activity. Abstract: The aim of this study was to analyze phenolic compounds and in vitro biological activity of seeds, skins and flesh of V. vinifera cultivars and interspecific hybrids grown in Poland. Their phenolic profile was analyzed using LC-PDA-MS-QTOF and UPLC-PDA-FL and 48 compounds were identified, including nine phenolic acids, one stilbene, 12 anthocyanins, 10 flavonols and 16 flavan-3-ols. Seeds and red skins showed the highest antioxidant activity as measured with ABTS, FRAP and ORAC assays and on-line profiling by HPLC-PDA coupled with post-column derivatization with ABTS. Regarding anticholinergic activity, seeds and skins demonstrated higher AChE than BuChE activity, contrary to the flesh, where the ratio was reversed. In all seeds and most skins and flesh samples, inhibitory activity against α-glucosidase was higher than that against α-amylase. In conclusion, the investigated grape elements may be attractive components of functional foods and nutraceuticals, and seeds – being by-products of the wine industry – can be utilized.